The influence of phase distribution and microstructure of the carbon steel on its chloride threshold value in a simulated concrete pore solution. (30th October 2020) - Torbati-Sarraf, H.; Poursaee, A.
Highlights: Heat-treatment was used to change the microstructure of conventional steel rebars. Pearlite and MnS are the most prone phases to corrosion initiation. Cementite fragmentation and isolation of pearlite restrict pit propagation. MnS refinement through cyclic heat-treatment retards pit nucleation. Abstract: The influence of steel microstructure and phase distribution on the corrosion initiation and chloride threshold value was investigated in a simulated concrete pore solution. Normalizing and cyclic heat-treatment were employed to change the grain size, pearlite, and MnS morphology of the conventional reinforcement carbon steel. The oxidation behavior of obtained microstructures was compared with non-treated steel specimens using the cyclic voltammetry technique. Chloride was added periodically in the solution, and threshold chloride value for each microstructure was determined using potentiostatic electrochemical impedance spectroscopy (EIS). Results revealed that the normalized steel lowered the chloride threshold value while cyclic heat treatment around eutectoid temperature increased the corrosion initiation resistance. Post-corrosion microscopic observation showed that corrosion initiated and propagated preferentially through the pearlite phase, while proeutectoid ferrite was intact. Isolating pearlite and fragmentation of cementite lamella and MnS inclusions through cyclic heat-treatment retarded pit nucleation and slowed down corrosion propagation.